Haemodynamic effects of percutaneous mitral valve edge‐to‐edge repair in patients with end‐stage heart failure awaiting heart transplantation. (30th July 2018) - Geis, Nicolas A.; Pleger, Sven T.; Bekeredjian, Raffi; Chorianopoulos, Emmanuel; Kreusser, Michael M.; Frankenstein, Lutz; Ruhparwar, Arjang; Katus, Hugo A.; Raake, Philip W.J.
Abstract: Aims: Functional mitral regurgitation is complicating end‐stage heart failure and potential heart transplantation by increasing pulmonary artery pressures. The aim of the present study was to investigate feasibility and haemodynamic effects of percutaneous mitral valve edge‐to‐edge repair using the MitraClip™ device in patients with end‐stage heart failure awaiting heart transplantation. Methods and results: In this retrospective study, we identified nine patients suffering from end‐stage heart failure listed for heart transplantation in whom moderate–severe or severe functional mitral regurgitation was recognized and treated with percutaneous mitral valve edge‐to‐edge repair. Twenty‐two patients listed for heart transplantation and presenting with moderate–severe or severe functional mitral regurgitation treated in the pre‐MitraClip™ era served as controls. Patients were analysed at two separate time points: MitraClip™ group: pre‐procedure and post‐procedure (follow‐up: 215 ± 53 days) and control group: study entry with recognition of moderate–severe or severe functional mitral regurgitation (follow‐up: 197 ± 47 days). Percutaneous mitral valve edge‐to‐edge repair with the MitraClip™ was feasible and safe in our high‐risk end‐stage heart failure population. The intervention resulted in significant reduction of mitral regurgitation (grade 3.0 [0.5] to 1.5 [0.5]; P = 0.009), left atrial diameter (51 mm [16] to 49 mm [4]; follow‐up MitraClip™ vs. control group P = 0.0497), pulmonary artery pressures (sPA 50 mmHg [15] to 45 mmHg [10]; P = 0.02; mPA 34 mmHg [8] to 30 mmHg [10]; P = 0.02), and New York Heart Association class (3.5 [1.0] to 3.0 [0.5]; P = 0.01) and improved mixed‐venous oxygen saturation (57% [11] to 55% [7]; follow‐up MitraClip™ vs. control group P = 0.02). No changes in the control group were observed. Conclusions: MitraClip™ implantation as 'bridge‐to‐transplant' strategy in patients with end‐stage heart failure and severe functional mitral regurgitation awaiting heart transplantation is feasible and appears to result in favourable haemodynamic effects.